Bidessus anatolicus adiyaman ssp. n. from Adıyaman province, southern Turkey (Coleoptera, Dytiscidae, Bidessini) - Aykut Medeni̇; Taşar Gani̇ Erhan; Fery, Hans (Zootaxa, 2021)
Bidessus anatolicus adiyaman ssp. n. is described from the Adıyaman province in southern Turkey. The taxon belongs to the unistriatus-group of the genus and can be separated from the nominotypical subspecies of Bidessus anatolicus Wewalka, 1972 by the broader body and the different shape of the male genitalia. The new taxon is illustrated in detail and photographs of the type locality and the surrounding area are given.